Commentary: Loin Pain Hematuria Syndrome - Bath, Natalie M. (J Rare Dis Res Treat, 2018)
Loin Pain Hematuria Syndrome (LPHS) remains a rare disease but has a significant impact on those affected by it. Patients diagnosed with LPHS experience severe, constant or intermittent flank pain that radiates to the groin and may be exacerbated even by a gentle touch. These patients often require significant narcotic regimens for pain control and are unable to maintain a functional lifestyle. Previously, diagnosis has been made based on clinical presentation. One treatment for this syndrome is renal autotransplant; however, success rates are varied. Therefore, patient selection for this procedure is important. We have developed the UW-LPHS test as a diagnostic maneuver in order to determine which patients with LPHS would benefit from renal autotransplant. To perform this diagnostic test, bupivacaine is instilled into the ureter on the affected side and left to dwell. Patients who experience pain relief following this test are deemed to benefit from renal autotransplant. Here we describe this novel diagnostic test and initial success rates following renal autotransplant.